Pembiayaan Porsi Haji Pegadaian Syariah dan Faktor-Faktor Yang Mempengaruhi Minat Nasabah (Studi Kasus : Nasabah PT. Pegadaian (Persero) Unit Pelayanan Syariah Madina) - Nasution, Ahmad Kurnia; Ilhamy, Muhammad Lathief (Universitas Labuhanbatu, 2021)
The purpose of this study is (1) What is the portion of Hajj financing in Sharia pawnshops,(2) factors driving customer interest in Sharia pawnshops and (3) Sharia pegadian marketing strategy.The object of this study is all customers who use the services of Madina Sharia pawnshops in 2022.The method of this study uses methods using data collection techniques and data processing techniques,data collection techniques using (1)literature studies,(2) Field Studies,(3) observation and (4) interviews.in data processing techniques researchers use (1) Editing (examination of data), (2) classifying (classification), (3) analyzing (analysis) and (4) Concluding (conclusion).The results of this study is the financing portion of Hajj financing Sharia services that provide convenience to the public to get the portion of Hajj portion of Hajj financing dalah one of the products of Sharia Pawnshop unit Madina.There are four factors that influence customer interest in Islamic pawnshops, namely service, location and marketing.How pawnshops introduce their products to Sharia pawnshops customers, namely place strategy, price strategy and promotion strategy.Â